Political values as a factor of social and political integration (Journal of Philosophy Culture and Political Science, 2018)
The article considers the problem of values, its theoretical significance and practical implementation in the various spheres of society. The article includes classification of values and defines feature of political values.The author revealed the basis for the formation of political values, the system of preferences as a set of elements of group consciousness, which is a significant factor in determining the initiation conditions, the determination of the entire political process.Key words: political values, political dialogue, political consciousness, the political needs and political interests.